Beckett on film - Beckett, Samuel; Asmus, Walter; Crowley, John; Egoyan, Atom; Eyre, Richard; Garrad, Charles; Hirst, Damien; Lindsay-Hogg, Michael; Highes, Enda; Jordan, Neil; Lefevre, Robin; Mamet, David; et al. (London : Clarence Pictures, 2001)
[v. 1.] Waiting for Godot / director, Michael Lindsay-Hogg (120 min.)##- Not I / director, Neil Jordan (14 min.)##- Rough for theatre I / director, Kieron J. Walsh (20 min.)##- Ohio impromptu / director, Charles Sturridge (12 min.)##- Documentary / producer, Larry Masterson ; director, Pearse Lehane (52 min.)##- [v. 2.] Krapp's last tape / director, Atom Egoyan (58 min.)##- What where / director, Damien O'Donnell (12 min.)##- Footfalls / director, Walter Asmus (28 min.)##- Come and go / director, John Crowley (8 min.)##- Act without words I / director, Karel Reisz (16 min.)##- [v. 3.] Happy days / director, Patricia Rozema (79 min.)##- Catastrophe / director, David Mamet (7 min.)##- Rough for theatre II / director, Katie Mitchell (30 min.)##- Breath / director, Damien Hirst (1 min.)##- That time / director, Charles Garrad (20 min.)##- [v. 4] Endgame / director, Conor McPherson (84 min.)##- Act without words II / director, Enda Hughes (11 min.)##- A piece of monologue / director, Robin Lefèvre (20 min.)##- Play / director, Anthony Minghella (15 min.)##- Rockaby / director, Richard Eyre (14 min.).
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Beckett, Samuel